Comparative effectiveness of microsurgery and endoscopic surgery in lumbar disc herniation: A systematic review and meta-analysis - Arifin, Jainal; Gani, Karina Sylvana; Kennedy, Dave (Narra Sains Indonesia, 2025)
Lumbar disc herniation, a common degenerative disc disease, adversely affects quality of life and often necessitates surgical intervention. Microsurgery and endoscopic surgery have emerged as alternatives to traditional open surgery, offering reduced pain and shorter recovery times. The aim of this study was to compare the outcomes of microsurgery and endoscopic surgery for lumbar disc herniation, evaluating effectiveness, safety, and patient-reported outcomes. A systematic search was conducted across six databases (EBSCOhost, OVID, ScienceDirect, Scopus, PubMed, and Cochrane) using terms related to lumbar disc herniation, spine injury, minimally invasive biportal endoscopic spine surgery, and conventional microscopic discectomy. The risk of bias was assessed using the Newcastle-Ottawa Scale (NOS), and a random-effects meta-analysis calculated mean differences (MD) and 95% confidence intervals (CI). Among the 267 studies screened, two studies met the inclusion criteria for a meta-analysis assessing the functional outcomes and safety of microsurgery and endoscopic surgery in patients with spinal disorders. The meta-analysis indicated that patients who received microscopic surgery had no significant difference in terms of operation time (MD: 3.48; 95%CI: -14.74 –21.70; p=0.71; I²=90%), postoperative drainage (MD: 16.28; 95%CI: -2.33–34.89; p=0.09; I²=47%), postoperative length of stay (MD: -1.26; 95%CI: -2.52–0.00; p=0.05; I²=77%), and postoperative C-reactive protein (CRP) levels (MD: -13.49; 95%CI: -36.85–9.87; p=0.26; I²= 97%) compared to those treated with endoscopic surgery. In conclusion, microscopic surgery and endoscopic surgery yield similar outcomes in terms of operation time, postoperative drainage, postoperative length of stay, and postoperative CRP levels. Therefore, the choice of techniques should be guided by patient-specific factors, surgeon expertise, and the facilities available at the healthcare center.